Hydroxyl Radical Induced Ultra-Weak Photon Emission from Tyrosine Solutions - Martin Bereta; Michal Cifra; Katerina Cervinkova; Ladislav Janousek; Jan Barabas (Communications - Scientific letters of the University of Zilina, 2015)
This paper deals with ultra-weak photon emission (UPE) from aqueous tyrosine solutions induced by hydroxyl radical. The physical nature of this specific phenomenon is presented and the proposed mechanism of its origin during oxidation of tyrosine is described. The experimental part of the work is focused on the measurements of intensity of ultra-weak photon emission from different solutions of tyrosine. The emission from solutions with and without presence of hydroxyl radical is analyzed. The results confirm the assumption that the highest intensity is detected from the solution of tyrosine, hydrogen peroxide and ferrous sulphate heptahydrate, likely due the Fenton reaction originated hydroxyl radical, which causes oxidation of tyrosine, formation of high-energy intermediates and electron excited species. Since hydroxyl radical induced ultra-weak photon emission from tyrosine has not been analyzed before in the available literature, our results could be the beneficial contribution to this field of research.